Early Marriage Culture and the Occurrence of Stunting in Toddlers in the Coastal Area of Sumenep Regency in 2024 - Yulia Wardita; Dian Permatasari; Cory Nelia Damayanti (International Journal of Health Engineering and Technology, 2024)
Wedding early still become phenomenon general social​ occurs in various regions in Indonesia , including districts Sumenep . Practice This Can impact big on health Mother And children , especially in matter nutrition And growth child . Stunting, or condition Where tall body child more low from standard age they consequence lack nutrition chronic , is Wrong One problem health main thing that can be done arise from wedding early. Study This aim For analyze connection between culture wedding early And stunting incidents in toddlers in the area coast Regency Sumenep on 2024. Methodology : Study This use design studies cross-sectional with approach quantitative . Sample study consists from mothers who married below​ 18 years old And own toddler aged 0-5 years in the area coast Regency Sumenep . Data collection via questionnaire And measurement anthropometry toddler . Data analysis was carried out with use test chi-square For determine connection between variable wedding early And stunting incident . Results study show that there is significant relationship​ between wedding early And stunting incidents in toddler . Mother who married below​ 18 years old own risk more tall For own child with stunting conditions compared with mothers who married at a young age more ripe . Factors like level education mother , economic status family , and access to service health Also join in influence stunting incident . Culture wedding early in the area coast Regency Sumenep contribute to its height stunting incidents in toddler . Required comprehensive intervention​ involve education society , improvement access service health , and strengthening policy For postpone age wedding To use reduce prevalence of stunting. Effort collaborative between government , institutions self-subsistent society , and community local very important For overcome problem This in a way effective.